Intersectionality in the Canadian Courts: In Search of a Decolonial Politics of Possibility - Caroline Alexandra Hodes (Atlantis)
This critical examination of intersectionality in the context of Canadian anti- discrimination cases outlines the Lockean foundations of identity construction in the courts. By framing Jasbir Puar’s articulation of intersectionality as an invitation to create more complex cartographies, the author challenges the hegemony of certain kinds of knowledge production in sites of institutional power.